2020
DOI: 10.1039/d0sc03663c
|View full text |Cite
|
Sign up to set email alerts
|

Shaping non-noble metal nanocrystals via colloidal chemistry

Abstract: Non-noble metal nanocrystals with well-defined shapes have been attracting increasingly more attention in the last decade as potential alternatives to noble metals, by virtue of their Earth abundance combined with...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 101 publications
0
27
0
Order By: Relevance
“…Nevertheless, well-controlled synthesis is able to produce narrow size/shape distributions. [7,17,[215][216][217] In the following, the application of Ni and CuNi nanoparticles supported on zirconia (ZrO 2 ) for methane reforming is discussed, [259][260][261][262] with operando NAP-XPS studies revealing reaction-induced surface composition changes. H r ∆ = + − ).…”
Section: Bimetallic Cuni Nanoparticles Supported By Zro 2 : Ch X -Indmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, well-controlled synthesis is able to produce narrow size/shape distributions. [7,17,[215][216][217] In the following, the application of Ni and CuNi nanoparticles supported on zirconia (ZrO 2 ) for methane reforming is discussed, [259][260][261][262] with operando NAP-XPS studies revealing reaction-induced surface composition changes. H r ∆ = + − ).…”
Section: Bimetallic Cuni Nanoparticles Supported By Zro 2 : Ch X -Indmentioning
confidence: 99%
“…Previous work along these lines mostly focused on metal clusters with up to about 100 atoms, representing the so-called non-scalable regime, in which nearly every atom counts. Three major synthesis routes were followed: i) clusters prepared and mass-selected in the gas phase, prior to "soft-landing" on suitable supports, [29][30][31][211][212][213][214] ii) colloidal size-and shape-controlled nanoparticles impregnated on various supports, [7,24,[215][216][217] and iii) wet-chemically prepared ligand-protected clusters in solution, [218][219][220][221][222][223][224] "size-purified" by size-exclusion-chromatography (SEC) or gel-electrophoresis prior to deposition on a support. Although the initial state of such monodisperse nanoparticles is well-defined, they typically undergo structural rearrangements and/or atom mobility during catalysis, which is why operando characterization is once more inevitable to understand their catalytic performance.…”
Section: Atomically-precise Au 38 Clusters Supported By Ceo 2 : Intracluster Restructuring and Atom Mobility During Co Oxidationmentioning
confidence: 99%
“…The growth of shaped-controlled nanoparticles critically depends on the applied synthesis conditions, and the reader is referred to reviews for in-depth accounts [55,68,69]. The size, shape, lattice structure and adsorption properties of the Pt and Pd NPs were evaluated by (HR-)TEM, aided by fast Fourier transform (FFT) analysis, XRD and CO-FTIR.…”
Section: Resultsmentioning
confidence: 99%
“…However, the efficiency and selectivity are still too low for industrial-scale implementation. [2,3] Hori and Takahashi et al have demonstrated that the Cu (100) facet facilitates the formation of ethylene while the Cu (111) facet favors methane generation. [4,5] This model catalyst study has inspired the exploration of colloidal Cu NCs with dominantly exposed (100) facets for enhancing CO 2 -to-C 2 H 4 selectivity.…”
Section: Introductionmentioning
confidence: 99%